Greek tragedy in action - Taplin, Oliver (Routledge, 2003)
Oliver Taplin's seminal study was revolutionary in drawing out the significance of stage action in Greek tragedy at a time when plays were often read purely as texts, rather than understood as performances. Professor Taplin explores nine plays, including Aeschylus' agamemnon and Sophocles' Oedipus the King. The details of theatrical techniques and stage directions, used by playwrights to highlight key moments, are drawn out and related to the meaning of each play as a whole. With extensive translated quotations, the essential unity of action and speech in Greek tragedy is.